An Analysis of Directive Speech Acts By Main Character In “Ke Jogja” Short Movie - Rizki, Lalu Satya Imam; Syamsurrijal, Syamsurrijal; Suktiningsih, Wiya (Jurnal Ilmu Sosial dan Humaniora, 2023)
The aim of this study is to identify the types of directive speech used by the main character in the short film "Ke Jogja". The research question focuses on the speech act that the main character performs towards his interlocutor. Qualitative methods have been used in this study and have led to the following observations. Firstly, a literature review that examines directive speech acts in films has been used to collect data. Data is gathered from conversations between the primary actors and their speech partners. Documentation techniques are then executed, followed by recording the movie script to use as a data source for literature review. The study revealed three categories of directive speech: asking (25%), telling (70%), and commanding. Telling was the most commonly used form of speech act in the film. The main character in the film frequently communicates his objectives to prevent misunderstandings arising from cultural and linguistic disparities. This study's results are anticipated to be valuable to a movie audience, as comprehension of a film's language patterns enhances viewers' appreciation of its objectives. On the contrary, studying speech acts may have real-life applications when observing the speech acts of speakers and conversational partners from diverse linguistic and cultural backgrounds.